2017
DOI: 10.5505/tjtes.2017.08839
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of some trace element levels (Zn, Fe, Mn, Mg, Cu, Cd, Co, Pb) in patients with burst fractures

Abstract: BACKGROUND: This study aimed to determine trace element levels (Zn, Fe, Mn, Mg, Cu, Cd, Co, and Pb) in patients with burst fractures in Van Province, Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…33,34 Beyond increases in general metabolic rate and energy expenditure, fracture induces changes in micronutrient metabolism that appear to be driven by an increased demand to facilitate callus formation and mineralization. This reactive response to fracture leads to decreased serum copper, 35,36 cobalt, 35,36 iron, 35,36 vitamin D, 37,38 and zinc, 35,36,[39][40][41] with the latter two accumulating in fracture tissue. Calcium metabolism is also perturbed, where it is mobilized from the intact skeleton through the concerted actions of the parathyroid hormone and the systemic inflammatory response to fracture.…”
Section: Metabolic Response To Fracturementioning
confidence: 99%
“…33,34 Beyond increases in general metabolic rate and energy expenditure, fracture induces changes in micronutrient metabolism that appear to be driven by an increased demand to facilitate callus formation and mineralization. This reactive response to fracture leads to decreased serum copper, 35,36 cobalt, 35,36 iron, 35,36 vitamin D, 37,38 and zinc, 35,36,[39][40][41] with the latter two accumulating in fracture tissue. Calcium metabolism is also perturbed, where it is mobilized from the intact skeleton through the concerted actions of the parathyroid hormone and the systemic inflammatory response to fracture.…”
Section: Metabolic Response To Fracturementioning
confidence: 99%
“…In a study on preterm and premature infants, maternal serum Mg level was found to be lower than healthy control group, whereas placental magnesium was found to be higher in the group presenting with PPROM but there was no statistically significant difference between umbilical cord magnesium levels and those in the healthy group [15]. In a study on patients with burst fractures, serum Mg levels were significantly lower than healthy control groups [17]. In this study on lip and oral cavity cancers, the difference between the patient and control group mean in terms of Mg levels was found to be statistically significant (p <0.05).…”
Section: Conclusion and Discussionmentioning
confidence: 90%
“…In a study conducted on Peyronie patients, it was found that the Cu levels in the blood serum of the patients were significantly lower than the healthy control groups [16]. In another study on patients with burst fractures, the Cu levels in blood serum of the patients were significantly lower than healthy control groups [17]. In a study on breast cancer, it was reported that the Cu and Mg levels in the blood of patients before and after radiotherapy were significantly different compared to the healthy control group [18].…”
Section: Conclusion and Discussionmentioning
confidence: 96%
See 2 more Smart Citations